Influence of temperature on high molecular weight poly(lactic acid) stereocomplex formation - M. Hortos; M. Vinas; S. Espino; J. J. Bou (eXPRESS Polymer Letters)
The influence of temperature on the formation of high molecular weight poly(lactic acid) (PLA) stereocomplex was studied by evaluation of the precipitates from dioxane solutions of PLA enantiomers (PLLA and PDLA). The racemic mixtures were characterized by Gel Permeation Chromatography, Infrared Spectroscopy, Differential Scanning Calorimetry, Scanning Electronic Microscopy, Wide-Angle X-ray Scattering and Vicat Softening Temperature. Precipitation was carried out under different solution temperatures, keeping constant the mixing ratio (XD), the molecular weight, the optical purity of both PLA enantiomers and the stirring rate. It was found that the precipitates contained only pure stereocomplex crystallites (racemic crystallites), without observing crystal phase separation between both homocrystals. The kinetics of the insoluble phase formation could be adjusted with the Avrami model, classically used for polymer crystallization in molten state. It was observed that the maximum PLA stereocomplex production rate was at about 40 °C. However, more thermally stable racemic crystallites were formed at high solution temperatures. It was found that all the precipitates were sphere-like at 10 g・dl–1 at the solution temperature of 25, 40, 60 and 80 °C.